The role of language in shaping religious practices and beliefs - Abd Salaam, Warid Thabrani (Journal of Religion and Linguistics, 2025)
Language is the most potent medium of communication, a conduit for expressing cultural ideals and ambitions, and a tool for preserving culture. Language serves as a crucial instrument for the acquisition and preservation of the identity of a specific group or community. This also influences the interplay between language conflict and theological conflict, as well as its exploitation by specific groups. We must employ language constructively to address the socio-cultural, linguistic, religious, and political requirements of the world. The study emphasizes that language and religion must be utilized positively, particularly in Malaysia, a multi-ethnic nation.